2016
DOI: 10.4239/wjd.v7.i3.34
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in migrants and ethnic minorities in a changing World

Abstract: On a worldwide scale, the total number of migrants exceeds 200 million and is not expected to reduce, fuelled by the economic crisis, terrorism and wars, generating increasing clinical and administrative problems to National Health Systems. Chronic non-communicable diseases (NCD), and specifically diabetes, are on the front-line, due to the high number of cases at risk, duration and cost of diseases, and availability of effective measures of prevention and treatment. We reviewed the documents of International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 93 publications
3
65
0
2
Order By: Relevance
“…In particular, people from first gear -to spiritualist -income body politic who have migrated to reside in high-income countries, appear to be more susceptible to overweight and obesity than their local anaesthetic counterparts (Delavari, et al 2013). Diabetes rates among migrant workers are triple higher rather indigenous universe (Montesi et al 2016). In Europeans, around 90% of males group and are higher more in female group which is 120%, this is equally same with the survey that have been done in Asian country.…”
Section: Discussionsupporting
confidence: 53%
“…In particular, people from first gear -to spiritualist -income body politic who have migrated to reside in high-income countries, appear to be more susceptible to overweight and obesity than their local anaesthetic counterparts (Delavari, et al 2013). Diabetes rates among migrant workers are triple higher rather indigenous universe (Montesi et al 2016). In Europeans, around 90% of males group and are higher more in female group which is 120%, this is equally same with the survey that have been done in Asian country.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, analysis of data on Asian sub-groups from the United States National Health Interview Survey between 1997 and 2008 indicate an upward trend in BMI and T2DM prevalence [23]. Data comparing diabetes prevalence rates by country, nationality and ethnicity are published regularly but interpretation of these can be problematic because of differences in the case definitions that are used, heterogeneity of the study populations and variable time periods of data collection [24, 25]. Nevertheless, compared to women in their home countries, the prevalence of T2DM amongst women in our study was much higher for South Asian women (16.7% versus 6%) [26] and Arab women (12.2% versus 4–8%) [27] but lower for Filipino women (1.7% versus 6%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…[1] The Centers for Disease Control and Prevention (CDC) reported that the prevalence of diabetes in the United States increased from 4.9% in 1990 to 11.3% in 2010, increased by 2.31 times. [2] Type 2 diabetes not only caused serious harm to human health, but also brought huge economic burden for individuals and countries. Diabetic nephropathy (DN) is one of the most common and severe microvascular complications of diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%